Advancing food integrity : GMO regulation, agroecology, and urban agriculture - Steier, Gabriela (Boca Raton : Taylor & Francis, 2017)
"The proliferation of Genetically Modified Organisms (GMOs) in our increasingly globalized food system is trivializing the inherent risks to a sustainable world. Responding to the realities of climate change, urbanization, and a GMO-dominated industrialized food system, Gabriela Steier's seminal work addresses the interrelationship of these cutting-edge topics within a scholarly, legal context. In Advancing Food Integrity: GMO Regulation, Agroecology, and Urban Agriculture, Steier defines food integrity as the optimal measure of environmental sustainability and climate change resilience combined with food safety, security, and sovereignty for the farm-to-fork production and distribution of any food product. The book starts with a discussion of the food system and explores whether private law has sufficiently protected food or whether public law control is needed to safeguard food integrity. It proceeds to show how the proliferation of GMOs creates food insecurity by denying people's access to food through food system centralization. Steier discusses how current industrial agricultural policy downplays the dangers of GMO monocultures to crop diversity and biodiversity, thereby weakening food production systems. Striving to promote agroecology by providing a fresh and compelling narrative of interdisciplinary questions, Steier explores how farming can be geared toward more sustainable and environmentally friendly practices worldwide in the future. This book belongs in the libraries of all those interested in food law, environmental law, agroecology, sustainable agriculture, and urban living practices."--Provided by publisher.
chapter 1 Food integrity and the food system defined -- chapter 2 The perspective switchboard: GMOs versus agroecology -- chapter 3 Food dependence: GMOs fail to feed the world -- chapter 4 Agrobiodiversity and agroecology: Contextualizing comparative GMO regulation -- chapter 5 The regulation of GMOs in international trade -- chapter 6 EU-US disputes over GMOs and the WTO biotech cases -- chapter 7 Concluding remarks: Obstacles to food integrity.
Keywords: Genetically modified foods -- Law and legislation; Agricultural ecology -- Law and legislation; Urban agriculture -- Law and legislation